Lamotrigine Induced Whole Body Tics: A Case Report and Literature Review - B. Centorino, Michael; Catalano, Glenn; C. Catalano, Maria (Current Drug Safety, 2016)
Lamotrigine is an anticonvulsant medication that also has utility in the treatment of bipolar disorder. It has been associated with many side effects, including rashes that can progress to Stevens-Johnson syndrome or toxic epidermal necrolysis. It has also been associated with the development of motor tics, most commonly in the head, neck, and shoulders. We will now present the case of a 45-year-old woman who developed tics that involved the entire left side of her body after her dose of lamotrigine was increased from 200 mg daily (2.0 mg/kg/day) to 225 mg daily (2.3 mg/kg/day). We will review the prior cases of lamotrigine induced tics, and compare them to the circumstances surrounding our patient. We will also discuss the neurobiology of tics and make suggestions to improve the tics, based on the reported cases.
Keywords: Anticonvulsant